Impact of Technical Integration of Target Cost and Production Time to Improve and Enhance Competitive Advantage - Sabri Sarhan, Hayder; Khudhair Abbas Alkhamees, Yas; Yousifmashkoorkadhim (International Journal of Psychosocial Rehabilitation, 2020)
The technical revolution here and the modern manufacturing environment have a significant impact on the development of the accounting field of costs represented by these new developments in the accounting field, especially those related to these techniques to manage the target cost and enhance competitiveness (such as the production system on time, the flashing system, total quality management, costs and management on the basis of activities, continuous improvement, target cost, advanced value engineering, benchmarking, constraint theory, and balanced scorecard). Where these technologies have been able to affect the accounting system at cost and on the recruitment of these technologies to serve both private business organizations (sophisticated and electronically controlled and the use of flexible and integrated manufacturing systems).